Rules-Based Fiscal Policy in France, Germany, Italy, and Spain - Daban Sanchez, Teresa (Occasional Papers; Occasional Paper ;, 2003)
Fiscal rules can help to counteract the deficits and spending biases that too often originate in the political process. Rules that constrain spending--rather than the balance--allow fiscal policy to be countercyclical. Yet the design of effective spending rules is by no means straightforward. Should a rule be real or nominal? How comprehensive should the definition of spending be? What safeguards ensure the credibility of a rule? How do rules work in decentralized systems where regions and states are partially autonomous? France, Germany, Italy, and Spain--countries that could benefit from more emphasis on fiscal rules to constrain spending--are explored here as case studies.